2009
DOI: 10.1088/1475-7516/2009/09/001
|View full text |Cite
|
Sign up to set email alerts
|

The torsion cosmology in Kaluza–Klein theory

Abstract: We have studied the torsion cosmology model in Kaluza-Klein theory. We considered two simple models in which the torsion vectors are Aµ = (α, 0, 0, 0) and Aµ = a(t) 2 (0, β, β, β), respectively. For the first model, the accelerating expansion of the Universe can be not explained without dark energy which is similar to that in the standard cosmology. But for the second model, we find that without dark energy the effect of torsion can give rise to the accelerating expansion of the universe and the alleviation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 98 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Taking into account the above reasons, in the following calculations, we will neglect the derivatives of γ n and we will consider as expression for γ n the one obtained in Eq. (99).…”
Section: Non Interacting Casementioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account the above reasons, in the following calculations, we will neglect the derivatives of γ n and we will consider as expression for γ n the one obtained in Eq. (99).…”
Section: Non Interacting Casementioning
confidence: 99%
“…Also in the interacting case, the expressions of γ n and γ ′ n are the same as the non-interacting case, given respectively in Eqs. (99) and (100). Instead, the expression of u ′ is given by:…”
Section: Interacting Casementioning
confidence: 99%
See 1 more Smart Citation
“…In the cosmology equations generated from those field equations, acceleration was not an independently prescribable initial condition. Chen and Jing [23] showed that those equations yield accelerating universe solutions without resorting to dark energy. They show that the model not only fits the supernovae data, but also solves the cosmic age problem of old high redshift objects [24].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Very soon it has been found that an interaction between the components of the universe can give desirable results, namely, can solve the cosmological coincidence problem and give appropriate behavior to the cosmological parameters. Considered forms of the interaction have phenomenological origin and mainly formed from the dimensional analysis (Guo, Z. K. et al 2005;Wei, H. et al 2006;Cai, R. G. et al 2005;Zhang, H. et al 2005;Wu, P. et al 2007;Chen, X. M. et al 2009;He, J. H. et al 2009;Chimento, L.P. 2009;Setare, M. R. 2006Setare, M. R. , 2007bJamil, M. et al 2008). It is not excluded that a fundamental theory explaining the origin of the interaction could be constructed when the nature of dark energy and dark matter will be established.…”
Section: Introductionmentioning
confidence: 99%